Cyclic microwave radiation synthesis, photoconductivity, and optical properties of CuInS2hollow sub-microspheres - Nawapong Chumha (2018)
© 2018 Elsevier B.V. CuInS2powder was synthesized by a cyclic microwave irradiation method using L-cysteine as a sulfur source. The effect of microwave power (180–600 W) on the purity, morphology, and particle size of the synthesized powders was investigated. X-ray diffraction (XRD) analysis showed that the synthesized powders were pure CuInS2with a tetragonal structure. Transmission electron microscopy (TEM) analysis revealed that the CuInS2powder synthesized at 180 W composed of solid microspheres with a diameter of about 250 nm. Increasing the microwave power to 300 W and 450 W transformed some of the sub-microspheres into hollow sub-microspheres. At 600 W, all of the CuInS2sub-microspheres were hollow. Based on time-dependent experiment, formation mechanisms of the CuInS2solid and hollow sub-microspheres were discussed. The photoconductivity of the CuInS2hollow sub-microspheres was greater than that of the CuInS2solid sub-microspheres, suggesting that the CuInS2hollow sub-microspheres were favorable to increase current carrier concentration and to improve electron transport. UV–vis diffuse reflectance spectrum (UV–vis DRS) of the CuInS2hollow sub-microspheres showed strong absorption intensity with a direct band gap energy of 1.48 eV, which is potentially useful in solar-light driven applications.